Мастер и Маргарита: роман / Михаил Булгаков - Булгаков Михаил Афанасьевич (Удмуртия, 1987)
Экземпляры: ф.12 (ретро) / Инвентарный номер: 18826 / Сис.шифр: 84(2Pос=Рус)6 / Авт.знак: Б 90 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6